INTERREG Rhine-Meuse Activities: An initiative for transnational high water prevention in the Rhine and Meuse area - Huttenloher, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Responding to the extreme floods of 1993/94 and 1995 on Rhine and Meuse the European Commission encouraged a transnational action programme to establish a preventive approach of flood protection within the Community Initiative INTERREG II C. The programme “INTERREG Rhine-Meuse Activities” (IRMA), jointly elaborated and implemented by the concerned states, should launch a new policy of flood prevention, based on spatial planning, and put it into action through concrete measures inside the entire catchment area. Even though the spatial planning orientation could not be observed absolutely strictly within the programme implementation, this initiative represents an important and successful first step towards a new direction of sustainable flood prevention policy.